The Effect of Government Transformation Programme on Government Investment: Evidence from Malaysia - Marzuki, Marziana Madah; Wahid, Khalid Abdul (Asian Journal of Empirical Research, 2022)
The study aimed to examine the effects of the Government Link Companies Transformation (GLCT) Programme in Malaysia on Government Link Investment Companies (GLICs) as the major shareholders of the Government Link Companies (GLCs). A series of semi-structured interviews were undertaken with key individuals from two GLICs in Malaysia. Our findings revealed that the existence of GLICs are still relevant as GLICs believed that their investments in GLCs are to protect the welfare of relevant parties of their institutions. The GLCT programme has not reduced the government’s share in GLICs, but instead it improved the governance and polished new talent management in GLICs. In addition, the study findings revealed that the improvement of GLICs after GLCT is due to effective leadership with good governance and integrity implemented in the GLCT. The findings are crucial to consistently enhance the effectiveness of Government Transformation Programmes (GTP) towards better performance among GLCs in Malaysia.